Alteration in soil fauna due to soil management and crop rotation in a long-term experiment - Krolow, Daniela da Rocha Vitoria; Krolow, Ivan Renato Cardoso; Rheinheimer, Danilo Danilo Dos Santos; Morselli, Tânia Beatriz Gamboa Araujo; Calegari, Ademir (Scientia Agraria, 2017)
The evaluation of the population of meso and macrofauna organisms has been receiving attention in different studies related to soil quality. Therefore, the present study had as objective to evaluate the population of macro and mesofauna organisms, in an experimental area installed for 26 years in Paraná / RS. Among the 11 existing treatments, six were selected by lot, grew in a Conventional and No-tillage system. Soil fauna organisms were captured at 10 cm depth. The method used for the extraction of edaphic organisms was Tüllgren funnel. The collections were executed in blocks and repetitions that represented 312 samples. In the autumn, 60,138 m-2 individuals were estimated, and in the summer they were 28,348 m-2 individuals. The adoption of the long-term no-tillage system favors the biodiversity of the soil fauna in relation to the soil that has been undergoing two years of cultivation and four annual harrows since 1976. The native forest soil is more biodiverse than the cultivated one. The most representative edaphic taxon in the autumn were Acari, Collembola and Diptera, and in the summer they were Acari, Collembola, Hymenoptera and Larva of Lepidoptera. The phytosanitary management of the areas influence the diversity indexes of the edaphic fauna. The soil moisture abiotic factor acts severely under the edaphic fauna in the summer, being more evident in the conventional cropping system. The collection season conditioned to the abiotic factors - soil moisture and temperature - influences the density of individuals, species richness and the Shannon and Pielou indexes.